Risk Management for Qatar Expressway Program - Abd Rahman, Nor Rozaini (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The construction of expressway projects associated with the various main risks such as political risks, legal risks, economic risks, cultural risks, and construction risks are considered critical and essential to be identified and mitigated in early stage for every minor or major projects. According to Dziadosz and Rejment (2015), the risk is a measurable part of uncertainty, for which we are able to estimate the occurrence probability and the size of damage. The risk is assumed as a deviation from the desired level. It can be positive or, which most often happens, it can be negative. Therefore, the risks analysis is so important for project selection and coordination of construction work. This paper identifies the level of severity of construction risks which had affected the implementation of the expressway/highway projects in Qatar. This research is also focused on the importance in practising the formality of risk management process by identifying the problems and difficulties associated with the projects risks, which includes obtaining the important information and suggestion the risk response in order to be used on future projects in the particular and focusing the risk mitigation in the early stage is necessary. There could be a possibility that the identified projects were not fully assessing the significant risk factors during feasibility studies, design stage, tender stage and construction stage. Based on a literature review, structured interviews with experts, unstructured interviews and detailed case studies, it was found that major participants agreed that the risk management process was satisfactorily adopted for ongoing and previous infrastructure projects in Qatar. The critical construction risk was design changes, new requirements, land acquisition, interfacing works and additional works which had caused the cost overrun and delay the completion works.